TOX Acts as a Tumor Suppressor by Inhibiting mTOR Signaling in Colorectal Cancer - Yang, Mengdi; Huang, Qianru; Li, Changcan; Jiang, Zhiyuan; Sun, Jing; Wang, Zhiyu; Liang, Rui; Li, Dan; Li, Bin; Zhao, Hui (Frontiers in Immunology, 2021)
The treatment and prognosis of advanced colorectal cancer (CRC) remain challenging clinical research focus. Here, we describe a new CRC tumor suppressor and potential therapeutic target: thymocyte selection associated high mobility group box (TOX) protein. The expression of TOX was lower in CRC than para-CRC. With the increase of tumor stage, TOX expression decreased, indicating the presence of TOX relates to better overall survival (OS). TOX suppressed the mechanistic target of rapamycin kinase (mTOR) signaling to inhibit cell proliferation, migration, invasion, and change the epithelial-mesenchymal transition (EMT) process. In addition, TOX promoted apoptosis. As tumor mutation burden and tumor microenvironment play vital roles in the occurrence and development of tumors, we analyzed the TOX expression in the immune microenvironment of CRC. The High TOX expression was negatively correlated with TumorPurity. Moreover, it was positively related to ImmuneScore, StromalScore, microsatellite instability (MSI) status, and Consensus Molecular Subtypes (CMS) 3 typing. Based on gene set enrichment analysis (GSEA), the reduced expression of TOX activates mTOR. We found rapamycin, an mTOR inhibitor, partly inhibited cell proliferation, invasion, and migration in shTOX HCT116 cells. Lastly, TOX suppressed tumorigenesis and lung metastasis of CRC in vivo. Rapamycin or combined with PD1 inhibitor is more effective than PD1 inhibitor alone in a tumor model. Taken together, these findings highlight the tumor-suppressive role of TOX in CRC, especially in MSI CRC, and provide valuable information that rapamycin alone or combined with PD1 inhibitor has therapeutic potential in CRC.